Selected legal aspects of surrogacy - Honzová, Ivana; Zemandlová, Anna; Prudilová, Leona; Prudil, Lukáš (Walter de Gruyter GmbH, 2020)
The aim of this article is to analyse the Czech legislation applicable to surrogacy cases while considering some basic social aspects. First the basic facts of surrogacy as a medical reproductive technique are discussed. Surrogacy is also considered as a social trend, and in terms of selected social aspects, such as the growing number of couples interested in surrogacy and their social status. Nevertheless, the main goal of the paper is to analyse selected legal problems as regards surrogacy and the Czech legislation. Therefore, the authors describe the basic legal framework that has relevancy to surrogacy cases (establishing parenthood and adoption) and identify the most frequent problems concerning surrogacy applications using three model cases. In the concluding remarks the adequacy of Czech legislation is discussed.
Keywords: surrogacy; adoption; IVF; ethics; family